Space-time matrix mathematical model of organization matrices convertion process in optoelectronic special processor - Zabolotna, N. I.; Dronenko, O. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The mathematical model of parallel method of conversion of long size matrices is developed in the article, for this purpose the existing method of reflection of mathematical models of matrix operations was extended by introduction of new operands, that allowed to represent specific features of block method. New structural model of parallel optoelectronic bit-cut special processor for matrices convertion by block method is developed which is characterized by the increase of productivity and extended functional possibilities.